1983
DOI: 10.1152/jn.1983.50.5.1098
|View full text |Cite
|
Sign up to set email alerts
|

Consistency and signal strength of respiratory neuronal activity

Abstract: The concerns of this study are taxonomic. We demonstrate a defining characteristic of respiratory neuronal activity. This characteristic is the degree or size of the respiratory component in the activity of a respiratory cell. The essential feature of respiratory activity is that it occurs in phase with some portion of the respiratory cycle. Therefore, neuronal activity can be arranged within a matrix in which the columns are fractions of the respiratory cycle and the rows are breaths and, as Netick and Orem (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 0 publications
0
62
0
Order By: Relevance
“…However, our previous study of RTN neurons underestimated RTN respiratory modulation for three reasons. Respiratory modulation was previously gauged using the 2 index (Orem and Dick, 1983), a less sensitive index than perievent histograms. We previously explored lower levels of CO 2 at which respiratory modulation is modest.…”
Section: Experimental Limitations: Comparison With Previous Resultsmentioning
confidence: 99%
“…However, our previous study of RTN neurons underestimated RTN respiratory modulation for three reasons. Respiratory modulation was previously gauged using the 2 index (Orem and Dick, 1983), a less sensitive index than perievent histograms. We previously explored lower levels of CO 2 at which respiratory modulation is modest.…”
Section: Experimental Limitations: Comparison With Previous Resultsmentioning
confidence: 99%
“…In one study of a small number of GG motor units in humans, Tsuiki and colleagues (2000) found units discharged during inspiration or both inspiration and expiration (see also Bailey et al 2005;and in rats, John et al 2005). However, no formal classification procedures were applied as used in other animal studies (Orem and Dick 1983). We hypothesized that there would be different populations of motoneurons with different firing properties that make up the overall pattern of human GG activity during respiration.…”
Section: Introductionmentioning
confidence: 99%
“…The database for this study was a subset from the databases used for our previously published studies [6,7,8,9,49,50,60]. The selection of the neurons and neuronal populations for this study was based on the duration of available spike trains (4000-65000 spikes).…”
Section: Methodsmentioning
confidence: 99%
“…The discharge of all the neurons was modulated to the rhythm of respiration. The measure of neuron involvement in respiration, η 2 [49], was in the range 0.5-0.9, for all neurons, except RM11 (η 2 = 0.12). The preferred phase of 67% of them was in the inspiratory phase of the cycle.…”
Section: Behavior-related Activity Of the Neuronsmentioning
confidence: 96%
See 1 more Smart Citation